APOE-ε4 Is Associated With Reduced Verbal Memory Performance and Higher Emotional, Cognitive, and Everyday Executive Function Symptoms Two Months After Mild Traumatic Brain Injury - Hellstrøm, Torgeir; Andelic, Nada; Holthe, Øyvor Øistensen; Helseth, Eirik; Server, Andres; Eiklid, Kristin; Sigurdardottir, Solrun (Frontiers in Neurology, 2022)
Background Substantial variance exists in outcomes after mild traumatic brain injury (MTBI), and these differences are not fully explained by injury characteristics or severity. Genetic factors are likely to play a role in this variance. Objectives The aim of this study was to examine associations between the apolipoprotein (APOE)-ε4 allele and memory measures at two months post-MTBI and to evaluate whether subjective cognitive and affective symptoms were associated with APOE-ε4 status. Based on previous research, it was hypothesized that APOE-ε4 carriers would show poorer verbal memory performance compared to APOE-ε4 non-carriers. Methods Neuropsychological data at two months post-injury and blood samples that could be used to assess APOE genotype were available for 134 patients with MTBI (mean age 39.2 years, 62% males, 37% APOE-ε4 carriers). All patients underwent computed tomography at hospital admission and magnetic resonance imaging four weeks post-injury. Results The APOE-ε4 + status was associated with decreased immediate memory recall (p = 0.036; β = −0.10, 95% CI [−0.19, −0.01]). Emotional, cognitive, and everyday executive function symptoms at two months post-injury were significantly higher in APOE-ε4 carriers compared to non-carriers. Conclusion The APOE-ε4+ allele has a negative effect on verbal memory and symptom burden two months after MTBI.